Assessment of Putative Bacteria as Probiotics in Juvenile Freshwater Prawn, Macrobrachium Rosenbergii (De Man) - Keysami, Mehran Avakh (2006)
A study focused on the use of putative bacteria as probiotics to reduce nutritional and disease problems in aquaculture industry was carried out. This study was conducted in 8 experiments to investigate juvenile M. rosenbergii putative bacterial flora as probiotics, for enhancement of growth and survival of juvenile M. rosenbergii during November 2002 to August 2005 at University Putra Malaysia. Bacterial counts and the putative bacterial flora in juvenile M. rosenbergii cultivation (0.1-9.0 g), were investigated and the isolated strains were classified to genera. Total viable cell counts were 96k2.6x104 CFUIml for culture water, 31 00kl69.0xl O4 CFUIml for culture tank sediment, 21 OO+143.0x104 CFUIml for prawn body surface, 14000k4.6x10~C FUIg for prawn digestive tracts and 5.6+2.8x104 CFUIg for prawn abdominal muscle. Altogether, 12 genera were identified from water, sediment and different organs of prawn. The most frequently isolated ones were Bacillus, Aeromonas and Pseudomonas. The three groups of putative bacteria (Bacillus subtilis, Micrococcus luteus and Corynebacterium ammoniagenes), collectively showed antagonistic activity against the six pathogens in antibacterial activity test. B. subtilis showed greatest inhibition of pathogens in well and disc diffusion assays and cross-streak method. Addition of 10 ml of cell free supernatant of B. subtilis to pathogens resulted in complete suppression of it within 12 h. Maximum growth and maximum zone of inhibition against A. hydrophila was observed at 30 OC and at pH 8 with 1 % NaCI, respectively. A ranking index (RI) was calculated to screen potential aquaculture probiont. The RI is based on the doubling time (td) and lag period (A) obtained from the growth profile of each bacterium. Three candidates (B. subtilis, M. luteus and C. ammoniagenes) and two pathogens (A. hydrophila and Pseudomonas aeroginosa) were grown in TSB broth and absorbance recorded at each 0.5 h during 24 h period. The B. subtilis grew equally as well as the pathogens and candidate B. subtilis had a faster specific growth rate (p=0.034) than the other candidates, M, luteus (0.031 ) and C. ammoniagenes (0.032) respectively. Sensitivity of juvenile prawns to two putative bacteria strains (B. subtilis and A. hydrophila) was examined using in vitro and in vivo pathogenicity challenge test. In vitro challenge test was done on juvenile prawn (0.1 g) using the immersion method. An in vivo challenge experiment was carried out using the feeding trial method. The result of in vitro and in vivo pathogenicity tests indicated that the survival of juvenile (0.1 and 0.45 g) was not affected by the presence of B. subtilis in fresh water but, A. hydrophila infected juvenile M. rosenbergii and cause about 78.67% mortality and exhibited disease clinical signs. A feeding trial was carried out to investigate the potential probiotic properties of B. subtilis and its suitable level in juvenile M. rosenbergii. Putative B. subtilis bacterium was added to commercial prawn feed as a probiotic. Six types of diets were prepared by mixing the prawn feed with Bacillus form in the ratio of 1:1, 2.1, 3:1, 4:l and 5:1, with an unsupplemented control. After 60 days, the prawns fed diet at level 3:1, showed a higher mean weight gain (593.45g) or 170.29% increase in growth over control. Clearly, feed treated with B. subtilis appeared to enhance growth and survival of M. rosenbergii at a ratio of 3:l. Another feeding trial was carried out to investigate the suitable methods of administration of B. subtilis to the commercial feed in juvenile M. rosenbergii culture. Four types of diets were prepared by mixing the prawn feed to Bacillus form in the ratio of 3:l with an unsupplemented as a control. The different methods used were blending, soaking, spraying and bathing. After 60 days, the prawns fed diet under soaking method treated group, showed a higher mean weight gain (1.49 g) or 142.28% increase in growth over control. To investigate the potential probiotic-ability of B. subtilis to combat the freshwater prawn diseases problem, B. subtilis bacterium was added to prawn feed as a probiotic at a level of 10" CFUIg feed by soaking method. Sixty days after the start of the B. subtilis feeding, the prawns were challenged by bath exposure to A. hydrophila (lo7 CFUIml). After 28 days of post challenge, B. subtilis treated group had 88.33% survival, whereas the control group had only 20.83% survival, with an unhealthy external appearance. After then a feeding experiment was conducted for juvenile M. rosenbergii (0.037 g) using three types of diets prepared with the incorporation of putative 8. subtilis, non-putative B. subtilis and a commercial probiotic at level of 101° (CFUIg) with an unsupplemented control. After 60 days the prawns fed putative B. subtilis added diets showed a higher suvival, mean weight gain (0.663_+0 .017g) with 0.267 g increase in growth over control and best FCR value (2.33 + 0.02 g). Finally, the probiotic-ability of the B. subtilis was evident from properties consisting dominant isolated one, greatest antagonistic activity against pathogenic agents, highest RI, non-pathogenic to the host, growth enhancement, health improvement and more effectiveness than non-putative and commercial probiotics. This study demonstrated that among putative bacterial flora of juvenile M. rosenbergii, B. subtilis can be a promising probiotic for this prawn.